Rancang Bangun Sistem Monitoring Stok Barang Berbasis Web untuk Meningkatkan Efisiensi Manajemen Persediaan Barang pada UMKM - Muhammad Rizqi Suhada; Yoki Muchsam; Angge Firizkiansah; Miri Ardiansyah (JIKOMTI : Jurnal Ilmiah Ilmu Komputer dan Teknologi Informasi, 2026)
Many MSMEs have not yet taken full advantage of technology, making stock management less effective. The proposed system is expected to reduce their workload while facilitating data-driven decision-making. Inefficient stock management remains one of the main obstacles for MSMEs, particularly when records are still handled manually. Such practices often result in data inconsistencies, delayed information, and disruptions to operational processes. The objective of this research is to design and develop a web-based stock monitoring system as a digital solution to enhance efficiency in inventory management, assist MSMEs in adopting technology for their businesses, and improve decision-making processes. The development process adopts the Waterfall model, which consists of requirement analysis, system design, implementation, and testing. The results demonstrate that the system can automatically record incoming and outgoing transactions, provide real-time stock data, and generate reports that simplify evaluation and decision-making. Black-box testing confirmed that all functionalities work as intended. The implementation of this system contributes to more accurate stock data, improved time efficiency, and easier access to information for MSMEs through web-based platforms. Therefore, this system is expected to be an effective digitalization solution for small and medium enterprises in managing their inventory.